New Biological Insights on X and Y Chromosome-Bearing Spermatozoa - Rahman, Md Saidur; Pang, Myung-Geol (Frontiers in Cell and Developmental Biology, 2020)
A spermatozoon is a male germ cell capable of fertilizing an oocyte and carries the genetic information for determining the sex of the offspring. It comprises autosomes and an X (X spermatozoa) or a Y chromosome (Y spermatozoa). The origin and maturation of both X and Y spermatozoa are the same; however, certain differences may exist. Previous studies proposed a substantial difference between X and Y spermatozoa; however, recent studies suggest negligible or no differences between these spermatozoa with respect to ratio, shape and size, motility and swimming pattern, strength, electric charge, pH, stress response, and aneuploidy. The only difference between X and Y spermatozoa lies in their DNA content. Moreover, recent proteomic and genomic studies have identified a set of proteins and genes that are differentially expressed between X and Y spermatozoa. Therefore, the difference in DNA content might be responsible for the differential expression of certain genes and proteins between these cells. In this review, we have compiled our present knowledge to compare X and Y spermatozoa with respect to their structural, functional, and molecular features. In addition, we have highlighted several areas that could be explored in future studies in this field.